Menuju hidup membiara yang seimbang - G. Huyghe (Yayasan Kanisius, 1968)
ir,jl.IV,c.1/oen, jil III,c.1/jil. IV,C.2, sgh Jil.I c1-2/jil.II=c1-2/jil.III c2-3,ws.jl.iv, c.3/stoc3=jl.1=c.1-2, jl2=c.1, jl3=c.1-3, jl.4=c.1-3